Yellow fever in colombia: a seminal investigation (1999)
The findings of Finlay in Cuba and Franco in Colombia, which enabled, at the beginning of the twentieth century, the identification of the cycles of urban and sylvatic yellow fever, respectively, illustrate the importance which a careful made observation about an indigenous problem can have as a starting point for new ideas and scientific developments.